Analisis Stilistik pada Puisi Sajak Tafsir Karya Sapardi Djoko Damono Berdasarkan Pendekatan Objektif - Rosmawaty Harahap; Alda Nafisa; Anggreiny Damanik; Atnes Hutagaol; Dian Sastra Sinaga; Gladys Felicia Manik; Rianggi Manalu; Mariana Yulistia Sinaga (Concept: Journal of Social Humanities and Education, 2024)
The poem Sajak Tafsir by Sapardi Djoko Damono is a literary work that uses simple language but is full of meaning. In this study, the author adopts an objective approach to explore the meaning of the poem. Objectively, the approach analyzed views literary works as objects that stand alone, without involving other elements outside them. This poem reflects an emotional journey filled with natural symbolism, such as the last leaf, wind, fire, and ash, to depict fear, fragility, and the sacrifice of love. Sapardi is famous for his invitation to interpret his poetry freely, therefore this analysis explores the meaning of the poetry as reflected in the natural metaphors and symbolism used.